Strategi Komunikasi Melalui Media Sosial Dalam Pembentukan Citra Balebengong Sebagai Media Jurnalisme Warga - Pradnya Yoni, Ni Luh Kade Diah; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
ABSTRAK The development of communication media these days leads to new challenges among media institutions. Writer interested in knowing the Strategy of BaleBengong on forming its image as a citizen journalism media through social media Twitter and Blog. Writer using descriptive qualitative method with snowball sampling to do this research. Through its social media account, BaleBengong invites people to share informations openly without any strict rules, but still with full responsibility. Balebengong’s communication strategy to form its image as citizen journalism media is poured verbally and non-verbally. Before the communication strategy is formed, Balebengong with the help of Sloka Institute, did a research about Balinese people’s habit on social media. Based on that research, BaleBengong then form its communication strategy, especially for through social media. Verbal communication strategy by BaleBengong showed on their tweets and blog article. BaleBengong name and logo was taken from a Balinese traditional building where people can speak their mind and share informations without any strict social barrier. Keywords: BaleBengong, Communication strategy, Image, Social media